BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN (STUDI KASUS PADA PT PRUDENTIAL LIFE ASSURANCE JAKARTA) - Cicih Ratnasih; Yolanda; Ukkap Johannes Siagian (Jurnal Manajemen FE-UB, 2022)
Abstract This research was conducted with the aim of knowing the effect of Brand Image and Quality of Customers who visit on Customer Loyalty of PT. Prudential Life Assurance Jakarta. The data used in this study are primary data collected through questionnaires and other literature studies. The population in this study were customers of PT. Prudential Life Assurance with a sample size of 100. The data analysis technique uses path analysis with the help of the SPSS 22 analysis system. The results showed that partially and simultaneously on Brand Image and Service Quality variables had a significant effect on Customers and Customer Loyalty.   Keywords: Brand Image, Service Quality, Customers and Customer Loyalty